O Projeto de Reorganização Nacional de Mário Augusto Teixeira de Freitas: estatísticas, território, Estado e Nação (1908-53) - Raul Amaro de Oliveira Lanari (2016)
Mário Augusto Teixeira de Freitas was an statistic born in Bahia, Brazil, who played an important whole towards the organization of this field in Minas Gerais' state administration during the 1920's and in the 30's for the federal government. His career was based on the combination between the "technical culture" and the belief that statistic should be seen as a scientific field capable of solving Brazilian society's problems and of guiding the country into modern times. From 1930 on, Teixeira de Freitas focused on the National Institute of Statistics foundation, which later evolved to be the Brazilian Institute of Geography and Statistics in 1938. Also, he dedicated himself to revise the geopolitical configuration of the country, to move the federal capital to the countryside, to fill demographic gaps, to hand more power to small towns and to establish educational policies that would stimulate the workforce specially in rural areas. Until his retirement in 1953, this man was part of the technical Brazilian elite and dialogued with key authoritarian nationalistic thinkers. His studies about the nation were read since the 1910's and received big visibility while President Getúlio Vargas was in power. The national statistics services consolidation process came along with Teixeira de Freitas' network expansion and the establishment of him as a public figure, always connected to nationalism. In the other hand, this idea of him don't take under consideration his interaction with Brazilian cultural elite's agenda at that time. The goal is to discuss Teixeira de Freitas connections in this scenario and the strategies used by him in order to implement his ideas / plans for the Statistics services in Brazil and the nation itself.